Iniciativas informacionais do Instituto Brasileiro de Informação em Ciência e Tecnologia (Ibict) em tempos da pandemia - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2020)
Open Access and Open Science are worldwide movements with potential benefits to the scientific process in all areas of knowledge. Aware of these benefits, and facing the pandemic caused by the new coronavirus, the Brazilian Institute of Information in Science and Technology (Ibict) carried out a series of initiatives with the objective of facilitating the finding of reliable scientific information sources on the subject. Among these initiatives, three are objects of study in this report: the Directory of scientific information sources of free access about the Coronavirus, the Preprint Repository Emerging Research Information (EmeRI) and the Network of Experts and Research. The three initiatives were developed by a multidisciplinary team in the areas of Information Science and Information Technology during the teleworking regime and based on a series of coordinated actions. The main results show that the tools developed are being accessed and used, however, the information in the Report points to the importance of making improvements in updating and maintaining systems, reflecting the need to modernize the strategies adopted by the development team, especially in the post-pandemic period.
Information initiatives of the BrazilianInstitute of Information on Science and Technology (Ibict) in pandemic times
Keywords: Ciência Aberta; Fontes de Informação; Comunicação Científica; Covid-19; Coronavírus; Processos de disseminação da informação